Impact of feeding mixture containing lupin meal on improvement of polyunsaturated fatty acids in egg yolk - Timová, Ivana; Straková, Eva; Všetičková, Lucie; Suchý, Pavel (Czech Journal of Animal Science, 2020)
The aim of the experiment was to determine how the content of lupin meal in the diet for commercial laying hens would affect the quality of fat in the egg yolk. A total of 210 Isa Brown laying hens was divided into three groups: the control group C (fed a mixture containing only soybean meal as a source of protein) and two experimental groups: EN 50% (fed a mixture containing 50% of soybean meal and 50% of white lupin seed meal, Zulika variety) and EN 100% (fed a mixture containing only white lupin seed meal as a source of protein). The results of the experiment using lupin seed meal in the feed mixture as a 50% and 100% replacement of extracted soybean meal confirmed the positive effect of lupin-based diets on egg yolk fat composition. Although the diets did not affect the fat content of the egg yolk, some other changes in the quality of the egg yolk were demonstrated during laying. These changes in egg yolk fat were characterized by a decrease (P ≤ 0.05) of saturated fatty acids (SFA), an increase (P ≤ 0.05) of monounsaturated fatty acids (MUFA), but only in some of them (C17:1 - heptadecenoic acid; C20:1n9 - eicosenoic acid and C22:1n9 - erucic acid) and, what is important, by a significant (P ≤ 0.05) increase of polyunsaturated fatty acids (PUFA) from the n-6 group (C18:2n6 - linoleic acid and C20:2n-6 - eicosadienoic acid) and n-3 group (C18:3n3 - α-linolenic acid; C20:5n3 - eicosapentaenoid acid and C22:5n3 - docosapentaenoic acid). From these results it is evident that using lupin meal in the feed mixtures for commercial laying hens increases the nutritional value and health benefit of the egg through the improvement of the levels of saturated and unsaturated fatty acids.
Keywords: fat content; health benefit; layers; Lupinus albus; omega-3; omega-6